Self-Confidence and Strategic Behavior - Gary Charness; Aldo Rustichini; Jeroen van de Ven (Center for Economic Studies and ifo Institute (CESifo), 2013)
We test experimentally an explanation of over and under confidence as motivated by (perhaps unconscious) strategic concerns, and find compelling evidence supporting this hypothesis in the behavior of participants who send and respond to others' statements of confidence about how well they have scored on an IQ test. In two-player tournaments where the highest score wins, one is likely to enter at equilibrium when he knows that his stated confidence is higher than the other player's, but very unlikely when the reverse is true. Consistent with this behavior, stated confidence by males is inflated when deterrence is strategically optimal and is instead deflated by males and females when hustling (encouraging entry) is strategically optimal. This behavior is consistent with the equilibrium of the corresponding signaling game. Based on the theory of salient perturbations, we propose a strategic foundation of overconfidence. Since overconfident statements are used in familiar situations in which it is strategically effective, it may also occur in the absence of strategic benefits, provided the environment is similar.
Keywords: A12; C91; D03; D82; 330; self-confidence; overconfidence; salient perturbations; analogies; strategic deterrence; unconscious behavior; self-deception; hustling; experiment